2015
DOI: 10.1037/fam0000083
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relations between constructive and destructive conflict and couples’ sleep.

Abstract: We examined longitudinal relations between interpartner constructive (negotiation) and destructive (psychological and physical aggression) conflict strategies and couples’ sleep over 1 year. Toward explicating processes of effects, we assessed the intervening role of internalizing symptoms in associations between conflict tactics and couples’ sleep. Participants were 135 cohabiting couples (M age = 37 years for women and 39 years for men). The sample included a large representation of couples exposed to econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 58 publications
(92 reference statements)
1
26
0
Order By: Relevance
“…For example, in Bagley et al (2016), concerns about community violence were associated with sleep efficiency and long wake episodes in expected directions, yet no effects for the full sample were observed for duration. Furthermore, other recent research has found stress exposure and psychological distress are often more strongly linked to sleep efficiency (eg, wake episodes) than sleep duration (eg, El-Sheikh, Kelly, & Rauer, 2013; El-Sheikh, Koss, Kelly, & Rauer, 2015). Additional studies are needed to further explicate the specific neighborhood-level predictors of sleep efficiency and total sleep duration, as well as the relative magnitude of effects on these different sleep parameters.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Bagley et al (2016), concerns about community violence were associated with sleep efficiency and long wake episodes in expected directions, yet no effects for the full sample were observed for duration. Furthermore, other recent research has found stress exposure and psychological distress are often more strongly linked to sleep efficiency (eg, wake episodes) than sleep duration (eg, El-Sheikh, Kelly, & Rauer, 2013; El-Sheikh, Koss, Kelly, & Rauer, 2015). Additional studies are needed to further explicate the specific neighborhood-level predictors of sleep efficiency and total sleep duration, as well as the relative magnitude of effects on these different sleep parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Couples’ sleep is also longitudinally related. Using the current study sample, El‐Sheikh, Kelly, Koss, and Rauer () found that wives’ sleep minutes and sleep latency (averaged across 7 days of actigraphy data) predicted their husbands’ sleep minutes and latency, respectively, 1 year later.…”
mentioning
confidence: 81%
“…For instance, unhappily married older adults’ sleep problems worsened across four years (Yang et al, 2013). More destructive and less constructive conflict spurred declines in actigraphy-assessed sleep quality and duration over one year (El-Sheikh et al, 2015). Marital discord also disturbs day-to-day sleep: on days when couple interactions were more negative, women experienced worse actigraphy-assessed sleep that night (Hasler and Troxel, 2010).…”
Section: Emerging Paths From Marital Distress To Health: Sleep and Mementioning
confidence: 99%
“…Accordingly, depression represents a key pathway from marital conflict and distress to disturbed sleep, a cardinal symptom of depression. In a longitudinal study, depressive symptoms explained conflict-related declines in sleep quality and duration (El-Sheikh et al, 2015). A known risk to partner well-being (Benazon and Coyne, 2000), depression also predicted worse sleep problems for partners one year later (Revenson et al, 2016, El-Sheikh et al, 2015).…”
Section: Emerging Paths From Marital Distress To Health: Sleep and Mementioning
confidence: 99%